دراسة الخواص المورفولوجية والإنتاجية لبعض هجن الفليفلة Capsicum annum L ضمن ظروف الزراعة المحمية - عكره أسماء (Latakia University Journal -Biological Sciences Series, 2018)
The purpose of research is to Study of the morphological and productive characteristics of some pepper hybrids (Capsicum annum L) in greenhouse. It used 5 hybrids, two hybrids are hot (FLASH, MESILLA), and three hybrids are sweet (POLARIS, NATASHA, MANGO). The research was carried out, during the cultivating season2015-2016 in Greenhouse unheated dimensions (8x50) m in Jableh region. It depended on the Randomized complete Block Design (RCBD) Full with five treatments (hybrids) and four replicates for each treatment, and 15 plants per replication The results showed different between studied hybrids in most studied indicators the power of vegetative growth, production amount, quality of the fruits, with superiority of hot hybrids in most productivity, quantity, quality characteristics, plant production, and fruit contain of dry matter, sugars and quantity of vitamin C. هدف البحث إلى دراسة الخواص المورفولوجية والإنتاجية لبعض هجن الفليفلة ضمن ظروف الزراعة المحمية. واستخدم في ذلك خمسة هجن، اثنان حريفة هي: FLASH ،MESILLA . وثلاثة هجن غير حريفة هي POLARIS، NATASHA، MANGO . نفذ البحث خلال الموسم الزراعي 2016 – 2015 ضمن بيت بلاستيكي غير مدفأ أبعاده (x 50 8) م في مدينة جبلة، اتبع في تنفيذ التجربة نظام القطاعات العشوائية الكاملة بخمسة معاملات (وهي الهجن) وبأربعة مكررات لكل معاملة وبمعدل(15) نباتاً في المكرر الواحد. أظهرت نتائج الدراسة تباين الهجن المدروسة في أغلب المؤشرات المدروسة من حيث قوة النمو الخضري، وكمية الإنتاج، ونوعية الثمار مع تفوق الهجن الحريفة في أغلب الصفات الإنتاجية والكمية والنوعية وإنتاج النبات، وبمحتوى الثمار من المادة الجافة والسكريات وكمية فيتامين C.